2008
DOI: 10.1007/s00417-008-0939-8
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic ophthalmia

Abstract: Sympathetic ophthalmia warrants prompt evaluation and treatment to maintain a favorable visual outcome. Ocular surgeries including vitreoretinal surgery and cyclodestructive procedures have been noted to be risk factors for the development of sympathetic ophthalmia. With current medical management including corticosteroids and immunomodulators visual prognosis is relatively good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 60 publications
2
90
0
7
Order By: Relevance
“…Subsequently, the symptoms spread from the injured right lower extremity to the opposite lower extremity and finally to the upper extremities. Although this observation appears to be similar to the process of sympathetic ophthalmia, the pathophysiology of which is considered to involve a T cell mediated autoimmune response (18,19), the mechanism involved in the present case is unclear. It is possible that local muscle inflammation triggered by physical damage may have contributed to the development of cGVHD-related myositis in the present case.…”
Section: Discussionmentioning
confidence: 61%
“…Subsequently, the symptoms spread from the injured right lower extremity to the opposite lower extremity and finally to the upper extremities. Although this observation appears to be similar to the process of sympathetic ophthalmia, the pathophysiology of which is considered to involve a T cell mediated autoimmune response (18,19), the mechanism involved in the present case is unclear. It is possible that local muscle inflammation triggered by physical damage may have contributed to the development of cGVHD-related myositis in the present case.…”
Section: Discussionmentioning
confidence: 61%
“…In der Literatur sind uneinheitliche Therapieschemata von 1 mg/kg Körpergewicht oraler Prednisolongabe bis zu initial 1000 mg intravenöser Verabreichung und langsamer Reduktion beschrieben [1,4,[6][7][8]. Eine langfristige Immunsuppression für insgesamt 6 bis 12 Monate wird empfohlen.…”
Section: Diskussionunclassified
“…Demographic and clinical features of the cohort were otherwise similar to those reported in earlier series. 7 The authors cited previous reports of both CSF pleocytosis and meningeal symptoms in patients with SO and reminded us that such findings may be more common than generally appreciated. They also pointed out that the presence or absence of CSF pleocytosis and meningeal symptoms should not be used to distinguish between SO from VKH disease.…”
mentioning
confidence: 99%
“…Best-corrected vision at last visit was 20/40 or better in 11 patients (57.9%) and 20/200 or worse in 3 (15.8%), figures generally in line with previous clinic-based cohorts. 7 The authors concluded that SO can be controlled in virtually all patients with an aggressive, step-wise approach to corticosteroid-sparing immunosuppressive therapy, and that prolonged drugfree remission can be achieved in a minority of patients.…”
mentioning
confidence: 99%